A Golgi-targeted off–on fluorescent probe for real-time monitoring of pH changes in vivo. Issue 47 (20th May 2019) - Fan, Li; Wang, Xiaodong; Ge, Jinyin; Li, Feng; Zhang, Caihong; Lin, Bo; Shuang, Shaomin; Dong, Chuan
Abstract : A Golgi-targeted small-molecular fluorescent probeRSG has been rationally designed for real-time monitoring of Golgi pH changes in vivo . Abstract : We present the first Golgi-targeted small-molecular pH-sensitive fluorescent probeRSG, which allows an off–on fluorescence response to Golgi acidification with high sensitivity and specificity.RSG has been successfully used for real-time monitoring of Golgi pH changes induced by drug treatment at the cellular level, as well as by the LPS-mediated inflammation in vivo .